Catholic discourse of Guilt in the construction of female subjectivity - Jiménez Argüello, Brenda (2021)
This work investigates the incidence of the religious discourse of Guilt in the construction of women’s subjectivities, taking as a reference the experience of four women from the Greater Metropolitan Area of Costa Rica. For this, theoretical and conceptual contributions of gender theory were used that allowed covering categories such as discourse, subjectivities, body and social control, which are necessary to understand Guilt within the power system from where it arises as a mechanism to produce effects in female subjectivities